No clear relationship between antihypertensive class and cognitive function over 12 months in a cohort study of community-dwelling adults aged 80 and over. (January 2019) - Peters, Ruth
Background: Hypertension is prevalent in older adults. Hypertension has also been associated with an increased risk of cognitive decline. However, evidence relating to the impact of antihypertensive use is mixed. Calcium-channel blockers (CCB) have been suggested as the most beneficial class of antihypertensive for protection of cognition in older adults, however, to date, there have been no cohort studies designed to examine this. Methods: Community-dwelling treated hypertensive adults aged 80 and over were recruited from general practice sites and followed for 1 year. Cognitive function was assessed at baseline and 12 months using the modified Mini-Mental State Exam (3MS). Regression was used to examine the association between 12-month exposure to antihypertensive class and change in cognitive function. Results: A total of 292 participants completed the study. Mean change in 3MS score was a rise of 0.53 [standard deviation (SD) 4.7] 3MS points in those taking CCBs ( n = 135) compared with a drop of 0.09 (SD 5.1) in those without ( n = 157) p = 0.28. There was no relationship between CCBs or between any antihypertensive class and change in cognitive function over 1 year. Additional analyses using a clinically meaningful fall of 5 or more 3MS points showed similar results. Conclusion: In a hypertensive community-dwelling older adult population treated with antihypertensives, there was no evidence that CCBs were protective of cognitive function over a 12-month exposure. If a protective effect is present, it may be small or require a longer treatment period. Larger longer studies are required for confirmation.